Social Media Dependency and the Dynamics of Social Interaction Among Adolescents: Analysis Based on William Glasser's Theory Using Storyboards - Ningsih, Dwi Rahayu; Wahyu Irawan, Andi (Psikoborneo: Jurnal Ilmiah Psikologi, 2025)
The advancement of information technology has led adolescents to engage intensively with social media, influencing the quality of their social interactions. This study aims to analyze the relationship between social media dependency and adolescents’ social interaction dynamics through William Glasser’s Choice Theory framework. A qualitative case study approach was employed, involving two vocational high school students selected through purposive sampling. Data were collected using in-depth interviews, participant observation, and storyboard techniques. The findings reveal that excessive social media use disrupts daily routines, fosters emotional dependency, and demonstrates the ambivalent role of social media as both a trigger for addiction and a source of self-motivation. Conversely, involvement in real-life activities, such as entrepreneurship, served as an adaptive mechanism to mitigate digital dependency. The analysis, based on Choice Theory, highlights that adolescents’ psychological needs fulfilled through social media remain superficial, underscoring the importance of balancing online and offline activities to support healthier social and emotional development.Kemajuan teknologi informasi telah mendorong remaja semakin intensif menggunakan media sosial, yang berdampak pada kualitas interaksi sosial mereka. Penelitian ini bertujuan menganalisis keterkaitan antara ketergantungan media sosial dengan dinamika interaksi sosial remaja melalui kerangka teori William Glasser. Metode penelitian menggunakan pendekatan kualitatif dengan desain studi kasus, melibatkan dua siswi SMK yang dipilih secara purposive. Data diperoleh melalui wawancara mendalam, observasi partisipan, serta teknik storyboard. Hasil penelitian menunjukkan bahwa penggunaan media sosial berlebihan dapat menimbulkan disrupsi pola hidup, ketergantungan emosional, serta ambivalensi fungsi media sosial sebagai pemicu kecanduan sekaligus motivasi perubahan diri. Temuan lain memperlihatkan bahwa keterlibatan dalam aktivitas nyata, seperti berjualan, mampu menjadi mekanisme adaptif untuk mengurangi ketergantungan pada media sosial. Analisis berdasarkan Choice Theory menegaskan bahwa pemenuhan kebutuhan psikologis remaja melalui media sosial cenderung bersifat semu, sehingga keseimbangan antara aktivitas daring dan luring menjadi krusial bagi perkembangan sosial dan emosional mereka.